Functional Bioink and 3D Bioprinting Tissue Scaffold Applications for Spinal Cord Injury - Yucer, Seydanur; Sarac, Begum; Ozarslan, Ali Can; Sakarya, Deniz; Ozerol, Esma Ahlatcioglu; Ciftci, Fatih (SPRINGER, 2026)
Spinal cord injury (SCI), commonly resulting from sudden trauma such as traffic or sports accidents, leads to severe disruption of axonal connections and loss of sensory and motor function below the injury site. Despite numerous therapeutic efforts, effective strategies for neural repair remain limited. Tissue engineering has emerged as a promising approach for axonal regeneration, particularly through the design of three-dimensional (3D) polymeric scaffolds that can restore the structural and functional integrity of the injured spinal cord. This review focuses on recent advances in biomaterials and scaffold designs developed for SCI repair, emphasizing the role of nanocomposite systems that combine graphene oxide (GO), synthetic polymers such as PLGA-PEG, and bioactive ceramics like hydroxyapatite (HA). These hybrid materials offer improved biocompatibility, mechanical matching with spinal tissue, and enhanced cellular adhesion and guidance cues for axonal growth. The synergistic integration of these components enables the fabrication of multifunctional scaffolds capable of supporting stem cell differentiation and neurotrophic factor delivery. By critically summarizing the key parameters influencing scaffold performance, such as microarchitecture, surface modification, and mechanical compliance, this work outlines a framework for developing next-generation 3D nanocomposite scaffolds for SCI regeneration. The proposed approach highlights how GO/PLGA-PEG/HA systems can bridge the gap between experimental tissue engineering and clinically translatable neuroregenerative therapies.
Keywords: Spinal cord injury; Axonal regeneration; Scaffold; Tissue engineering; Graphene oxide; Synthetic polymers; Hydroxyapatite; POLY-EPSILON-CAPROLACTONE; NERVE REGENERATION; GUIDANCE; CELLS; DELIVERY; ACID; Engineering